Stability of freeze-dried plasma prepared from patients on oral anticoagulants - Brozović, Milica (1973)
The suitability of freeze-dried plasmas from patients on oral anticoagulants to serve as reference material in the calibration of thromboplastins used in the control of oral anticoagulant treatment was assessed in two centres. One pooled normal plasma and four pooled plasmas from patients at different levels of anticoagulation were collected into HEPES-citrate containing Trasylol. The plasmas, in 1 ml volumes, were freeze dried in siliconized ampoules under the optimal conditions used for biological standards. Small aliquots of the same plasmas were stored at −70°C. Five different thromboplastins were used to carry out the tests on these plasmas. There was little difference in the clotting times obtained with five reference thromboplastins (two human, two rabbit, and one bovine reagent) on frozen and freeze-dried plasma, if the latter was tested immediately after complete reconstitution or within six hours of reconstitution if kept at +4°C. Reconstituted plasmas showed a marked shortening of clotting times when stored at 22 and 37°C if thromboplastins sensitive to activation of factor VII were used. In contrast, when thromboplastins sensitive to factor V were used, prothrombin times in plasmas stored at 22 and 37°C became prolonged due to the loss of factor V. Freeze-dried plasmas from patients on oral anticoagulants can be used to calibrate thromboplastins, provided they are used immediately after complete reconstitution or kept at +4°C for use within four to six hours of reconstitution.